Abiotrophia defectiva bacterial endocarditis complicated by an infective intracranial mycotic aneurysm - The need for aggressive odontogenic source control - Dong Tony Cheng; Paul Mercedes Kim; Thomas Young; Dimitrios Nikolarakos (Elsevier, 2022)
Abiotrophia defectiva or nutritionally variant streptococci (NVS) was first described in 1961 as a rare cause of infectious endocarditis (IE). It is distinct to the Streptococcus genus, pleomorphic, and demonstrates variable Gram-staining characteristics due to poor growth in culture media requiring extended incubation or 16S rRNA sequencing in culture negative situations.1 NVS has also been implicated in the pathogenesis of culture-negative endocarditis. In comparison with other causes of endocarditis, it has the ability to secrete exopolysaccharide and adheres to fibronectin in the extracellular matrix of endovascular structures.2 NVS is associated with significant morbidity and mortality, higher rates of multisystem complications ranging from pancreatic abscess, intracranial aneurysms, osteomyelitis, and valvular destruction, despite sensitivity to antibiotics.